Recovery from Maunder-like Grand Minima in a Babcock-Leighton Solar Dynamo Model - Karak B.B.; Miesch M. (My University, 2025)
The Sun occasionally goes through Maunder-like extended grand minima when its magnetic activity drops considerably from the normal activity level for several decades. Many possible theories have been proposed to explain the origin of these minima. However, how the Sun managed to recover from such inactive phases every time is even more enigmatic. The Babcock-Leighton type dynamos, which are successful in explaining many features of the solar cycle remarkably well, are not expected to operate during grand minima due to the lack of a sufficient number of sunspots. In this Letter, we explore the question of how the Sun could recover from grand minima through the Babcock-Leighton dynamo. In our three-dimensional dynamo model, grand minima are produced spontaneously as a result of random variations in the tilt angle of emerging active regions. We find that the Babcock-Leighton process can still operate during grand minima with only a minimal number of sunspots, and that the model can emerge from such phases without the need for an additional generation mechanism for the poloidal field. The essential ingredient in our model is a downward magnetic pumping, which inhibits the diffusion of the magnetic flux across the solar surface. © 2018. The American Astronomical Society. All rights reserved..